Bifunctional naringenin-laden gelatin methacryloyl scaffolds with osteogenic and anti-inflammatory properties - Cardoso, Lais M. (2024)
Objective: To fabricate and characterize an innovative gelatin methacryloyl/GelMA electrospun scaffold containing the citrus flavonoid naringenin/NA with osteogenic and anti-inflammatory properties. Methods: GelMA scaffolds (15 % w/v) containing 0/Control, 5, 10, or 20 % of NA w/w were obtained via electrospinning. The chemical composition, fiber morphology/diameter, swelling/degradation profile, and NA release were investigated. Cytotoxicity, cell proliferation, adhesion and spreading, total protein/TP production, alkaline phosphatase/ALP activity, osteogenic genes expression (OCN, OPN, RUNX2), and mineralized nodules deposition/MND with human alveolar bone-derived mesenchymal stem cells (aBMSCs) seeded on the scaffolds were assessed. Moreover, aBMSCs seeded on the scaffolds and stimulated with tumor necrosis factor-alpha/TNF-α were submitted to collagen, nitric oxide/NO, interleukin/IL-1α, and IL-6 production assessment. Data were analyzed using ANOVA and t-student/post-hoc tests (α = 5 %). Results: NA-laden scaffolds presented increased fiber diameter, lower swelling capacity, and faster degradation profile over 28 days (p < 0.05). NA release was detected over time. Cell adhesion and spreading, and TP production were similar between GelMA and GelMA+NA5 % scaffolds, while cell proliferation, ALP activity, OCN/OPN/RUNX2 gene expression, and MND were higher for GelMA+NA5 % scaffolds (p < 0.05). Cells seeded on control scaffolds and TNF-α-stimulated presented higher levels of NO, IL-1α/IL-6, and lower levels of collagen (p < 0.05). In contrast, cells seeded on GelMA+NA5 % scaffolds showed downregulation of inflammatory markers and higher collagen synthesis (p < 0.05). Significance: GelMA+NA5 % scaffold was cytocompatible, stimulated aBMSCs proliferation and differentiation, and downregulated inflammatory mediators’ synthesis, suggesting its therapeutic effect as a multi-target bifunctional scaffold with osteogenic and anti-inflammatory properties for bone tissue engineering.